Answers

2015-01-15T23:31:17+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
the functions inside the Latex script are not being interpreted properly by the Interpreter of the language - today..  there were many other questions - with same difficulty.  So I have changed the answer.  please understand the logic. thanks.

Let
Sin^{-1}x=A, Sin^{-1}(1-x)=B, Cos^{-1}(x)=C\\x=SinA, 1-x=SinB, x=CosC\\CosA=sqrt{(1-x^2)},\\ CosB=sqrt{(1-(1-x)^2)}=sqrt{(2x-x^2)}\\SinC=sqrt{(1-x^2)}\\\\Given,. A+B=C\\...Sin(A+B)=SinC\\SinACosB+SinBCosA=SinC\\

x* sqrt {(2x-x^2)}+(1-x)* sqrt{(1-x^2)}=sqrt{(1-x^2)}\\ x*sqrt{(2x-x^2)}=x*sqrt{(1-x^2)}\\x=0.. is-a-solution\\2x-x^2=1-x^2\\2x=1\\x=1/2\\

So you have two solutions  x =  0 and 1/2.

1 5 1
some problems with equation editor - LaTex interpreter today. I had to rewrite to be able to display like above.